2023
DOI: 10.5195/jmla.2023.1513
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies among Scopus and Web of Science, coverage of funding information in medical journal articles: a follow-up study

Abstract: Objective: This follow-up study aims to determine if and how the coverage of funding information in Web of Science Core Collection (WoS) and Scopus changed from 2015 to 2021. Methods: The number of all funded articles published in 2021 was identified in WoS and Scopus bibliographic databases using bibliometric analysis on a sample of 52 prestigious medical journals. Results: The analysis of the number of funded articles with funding information showed statistically significant differences between Scopus and Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Another important indicator of the research state of a scientific field/sub-field is research funding [17]. Our analysis showed that 41.1% of papers are funded, which is notably more than in many other disciplines [18], however, less than in a comparable subfield, namely the use of AI in pediatrics, where 47.4% of papers were funded [2].…”
Section: Resultsmentioning
confidence: 81%
“…Another important indicator of the research state of a scientific field/sub-field is research funding [17]. Our analysis showed that 41.1% of papers are funded, which is notably more than in many other disciplines [18], however, less than in a comparable subfield, namely the use of AI in pediatrics, where 47.4% of papers were funded [2].…”
Section: Resultsmentioning
confidence: 81%
“…Another important indicator of the research state of a scientific field/sub-field is research funding [22]. Our analysis showed that 41.1% of papers are funded, notably more than in many other disciplines [18]; however, less than in a comparable sub-field-namely, the use of AI in pediatrics, where 47.4% of papers are funded [2].…”
Section: Most Prolific Funding Bodiesmentioning
confidence: 86%
“…Additionally, some parts of the study were qualitative, which might have resulted in a slight bias in research theme identification and naming. Finally, the funding information in Scopus might contain some inaccuracies [72], but this seems to have been reduced recently [73].…”
Section: Study Limitationsmentioning
confidence: 99%